Proliferation and metabolic activity of the Atlantic sturgeon cell line AOXlar7y under short-term serum-reduced conditions, and the effect of stimulation with growth factors and cytokines - Di Leonardo, Valeria; Brenmoehl, Julia; Wanka, Heike; Grunow, Bianka (Frontiers in Toxicology, 2025)
IntroductionFish cell lines represent a powerful tool for studying the biology and toxicology of aquatic species in compliance with the 3Rs principles. In addition, they hold potential for more advanced biotechnological applications. However, fish cell cultures are mainly cultivated with fetal bovine serum. Therefore, in this study, we investigated the impact of serum reduction and the effects of six growth factors and cytokines on a sturgeon larval cell line (AOXla7y), which has been previously proven to be a valuable model for climate change and toxicology studies.MethodsThe serum reduction (from 10% to 5% and 2%) and the addition of two concentrations (10 and 50 ng/mL) of six growth factors and cytokines (FGF-2, IGF-1, LIF, IFN-γ, IL-13, and IL-15) to the 2% serum growth medium were evaluated over 6 days of cultivation. The morphology and cell density were determined using phasecontrast images after the experiment ended, while real-time label-free cell impedance (xCELLigence) was recorded throughout the cultivation period. Moreover, the end-point oxygen consumption in basal and uncoupled respiration conditions was analyzed with the Seahorse XF Cell Mito Stress Test Kit.ResultsThe results demonstrated a general adaptation of the sturgeon cell line to a serum-reduced environment and the modulatory effects of growth factor and cytokine supplementation on cell growth and metabolism.DiscussionThese findings suggest that the sturgeon cell line has the potential to transition to a serumfree medium without major observed morphological modifications and with a limited reduction in proliferation. Its metabolism was differentially modulated by the signaling of growth factors and cytokines and exhibited a variable metabolic phenotype under mitochondrial stress. This study provides a characterization of the Atlantic sturgeon cell metabolism and offers a preliminary assessment for developing an animal-free and chemically defined medium.